Design And Build Control Of Home Electronic Devices Wirelessly Based On Arduino: Rancang Bangun Kendali Perangkat Elektronik Rumah Secara Wireless Berbasis Arduino - Ahmad Jurnaidi Wahidin; Galih Anggara Putra (SYSTEMATICS, 2022)
In a house or building that has a lot of room, of course there are also lots of electronic devices, electronic devices have several different switch locations that make someone have to approach the location to turn on or turn off the electronic device. The human forgetting factor is also a problem in this case. In order to support work efficiency, time and electrical resources, the author conducted research on controlling home electronic devices using wireless using Arduino. This tool serves as a substitute for a conventional switch. Control circuit that can be connected to wifi to turn on and off electronic devices such as lights, air conditioners, fans, dispensers, water pumps and so on. Through the design of this tool, a person can turn on or turn off an electronic device through a smartphone or computer from anywhere as long as it is still connected to the same wifi network as the controller.